2021
DOI: 10.3389/fnins.2021.761654
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oxygen Metabolism and Haemodynamics in Patients With Multiple Sclerosis and History of Optic Neuritis

Abstract: Vascular changes and alterations of oxygen metabolism are suggested to be implicated in multiple sclerosis (MS) pathogenesis and progression. Recently developed in vivo retinal fundus imaging technologies provide now an opportunity to non-invasively assess metabolic changes in the neural retina. This study was performed to assess retinal oxygen metabolism, peripapillary capillary density (CD), large vessel density (LVD), retinal nerve fiber layer thickness (RNFLT) and ganglion cell inner plexiform layer thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…This is of particular importance because oxygen metabolism and blood flow are strongly coupled, and hypoxia causes counterregulatory vasodilation (55). Furthermore, we have validated our approach in previous studies and successfully used this method to assess oxygen extraction in patients with type 1 diabetes (21) as well as in patients with systemic neurodegenerative and neuroinflammatory diseases (59,60).…”
Section: Discussionmentioning
confidence: 77%
“…This is of particular importance because oxygen metabolism and blood flow are strongly coupled, and hypoxia causes counterregulatory vasodilation (55). Furthermore, we have validated our approach in previous studies and successfully used this method to assess oxygen extraction in patients with type 1 diabetes (21) as well as in patients with systemic neurodegenerative and neuroinflammatory diseases (59,60).…”
Section: Discussionmentioning
confidence: 77%
“…Based on reflectometric measurements of the oxygen saturation in retinal vessels together with the determination of total retinal blood flow using Doppler optical coherence tomography, we can draw conclusions on the oxygen metabolism of the retina without invasive measurements. We have successfully used this approach in previous studies to investigate oxygen metabolisms in healthy subjects [ 55 , 56 ] as well as in pathological conditions [ 44 , 57 ]. As all techniques used in the current study are non-invasive and thus well tolerated, this approach is also suitable for larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we combined these results into a single study. Ultimately, this meta-analysis included 13 studies with 996 MS eyes and 847 HC eyes (Lanzillo et al, 2018;Feucht et al, 2019;Cennamo et al, 2020;Cordon et al, 2020;Farci et al, 2020;Murphy et al, 2020;Ulusoy et al, 2020;Yilmaz et al, 2020;Aly et al, 2021;Kallab et al, 2021;Khader et al, 2021;Montorio et al, 2021;Rogaczewska et al, 2021a,b). Murphy et al (2020) reported the results…”
Section: Included Studies and Main Characteristicsmentioning
confidence: 99%
“…stratified by image artifact grading, and we only included the data of minimal artifact in the quantitative analysis of meta-analysis. Among 13 included studies, four studies (Cordon et al, 2020;Farci et al, 2020;Kallab et al, 2021;Khader et al, 2021) analyzed monocular data, whereas nine studies (Lanzillo et al, 2018;Feucht et al, 2019;Cennamo et al, 2020;Murphy et al, 2020;Ulusoy et al, 2020;Yilmaz et al, 2020;Aly et al, 2021;Montorio et al, 2021;Rogaczewska et al, 2021a,b) analyzed biocular data. For patients with MS, the mean illness duration ranged from 4 to 11 years and the mean EDSS scores ranged from 1.0 to 3.5.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation